2015
DOI: 10.1016/j.bbamcr.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of PTK7 on KDR activity in endothelial cells and angiogenesis

Abstract: Protein tyrosine kinase 7 (PTK7) is a member of the defective receptor protein tyrosine kinase family which lacks catalytic activity. Expression of PTK7 is increased in various cancers but its role in carcinogenesis is not well understood. We previously showed that disruption of PTK7 function suppresses VEGF-induced angiogenic phenotypes in HUVECs and mice. Here, we investigated molecular mechanisms for modulating VEGF-induced physiological effects by PTK7. Treatment with a high concentration of extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…The mechanism(s) underlying the contradictory roles played by PTK7 in different cancer types is unclear. Recently, we demonstrated that PTK7 displays phenotypes ranging from oncogenic to tumor-suppressive depending on its concentration relative to those of its binding partners, such as kinase insert domain receptor (KDR) [17]. Our finding of a biphasic function of PTK7 explains in part the discrepancy in the expression-level-dependent oncogenic functions of PTK7.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The mechanism(s) underlying the contradictory roles played by PTK7 in different cancer types is unclear. Recently, we demonstrated that PTK7 displays phenotypes ranging from oncogenic to tumor-suppressive depending on its concentration relative to those of its binding partners, such as kinase insert domain receptor (KDR) [17]. Our finding of a biphasic function of PTK7 explains in part the discrepancy in the expression-level-dependent oncogenic functions of PTK7.…”
Section: Introductionmentioning
confidence: 84%
“…It was well known that HER3, a catalytically defective RPTK, can heterodimerize with other EGFR family members upon ligand binding such as neuregulin and activates downstream signaling proteins such as Akt and Erk [28]. We have previously demonstrated that PTK7 binds to and activates KDR, one of VEGF receptor [17]. However, KDR expression was not detectable in TE-10 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternately, the therapeutic effect of Vatalanib may be due to inhibition of KDR. There is a biphasic relationship between PTK7 expression and KDR activity such that there is an optimal PTK7 concentration that leads to higher KDR activity (38). The therapeutic effect of Vatalanib might be due to the inhibition of KDR, which in ATRT cells may have higher activity due to increased levels of PTK7.…”
Section: Discussionmentioning
confidence: 99%